A Meta-Heuristic Hybrid Algorithm for the Rich Vehicle Routing Problem - Moschos, Evangelos; Ponis, Stavros T.; Rokou, Elena (ExcelingTech, 2020)
This paper presents an enriched variation of the original Vehicle Routing Problem (VRP), in which traffic zones, CO2 emissions and heterogeneity of vehicles are all taken into consideration. The objective of the model is to minimize the total travelled distance, while assigning specific customers to specific type of vehicles and maintaining the emissions of the entire fleet under a specified limit. The proposed hybrid algorithm (TDHF-GVRP) is composed of two nested genetic algorithms, interacting with each other as well as with other local search optimization methods. The external genetic algorithm (parent) is responsible for the assignment of customers to vehicle types, whereas the internal (child) algorithm is responsible for solving the vehicle routing problem for each category of vehicles separately.